Accounting Reporting Problems – Interim Financial Statements (Book). - Burns, Thomas J.; Kiger, Jack E. (The Accounting Review, 1979)
Abstract Reviews the book "Accounting Reporting Problems–Interim Financial Statements," by Michael Schiff.